INOVASI PERTUNJUKAN MILENIAL GAMELAN X SLANK - Darmawan, Iwan (Narada : Jurnal Desain dan Seni, 2025)
The collaboration of traditional and modern musical arts continues to develop in the millennial era as an effort to preserve, develop culture while bringing gamelan culture closer to young audiences. This paper discusses the concept of the performance process of Millennial Gamelan X Slank, a performance art innovation show that combines traditional gamelan instruments with the legendary band Slank as a symbol of modern music style equipped with visual design arrangements and contemporary background dancers. This collaboration aims to show the millennial generation the harmony between traditional music and modern music and bridge generations in understanding the cultural values of gamelan. Through the implementation of the concept of Millennial Gamelan X Slank is an art performance to explore the musical aspects and multidisciplinary creativity of the arts towards strengthening culture through performing arts.